РАСЧЁТ ПАРАМЕТРОВ СИММЕТРО-КОМПЕНСИРУЮЩЕГО УСТРОЙСТВА ТРЁХФАЗНОЙ СИСТЕМЫ ЭЛЕКТРОСНАБЖЕНИЯ НА ОСНОВЕ ДЕКОМПОЗИЦИИ СИСТЕМЫ - Ягуп, В.Г.; Ягуп, Е.В. (Інститут електродинаміки НАН України, Київ, 2016)
The method of calculating parameters of symmetry-compensating device for three-phase power supply system based on the decomposition of the system is proposed. The system is divided into three parts, representing the power source, load and symmetry-compensating device. Processes in each part are considered separately, which significantly simplifies the analysis .Operation full compensation is determined by the active power balance conditions. Parametric synthesis of symmetry-compensating device is carried through by means of optimization methods that are easily implemented in packages of computer mathematics. Application of the method is illustrated by the examples of three-wire and four-wire power supply systems. References 7, figures 5.